Electric Field Effects During Solidification of the Ternary Oxide Eutectic Al2O3‐YAG‐ZrO2. Issue 5 (6th April 2018) - Cherif, M.; Hicher, P.; Benamara, O.; Lebbou, K.; Haumont, R.; Duffar, T.
Abstract: LHPG and zone melting solidification of Al2 O3 ‐YAG‐ZrO2 :Y eutectic samples is performed in order to investigate intrinsic and extrinsic electric field phenomena. An intrinsic electric field is measured during solidification. Its decay with distance from the interface, and its relaxation with time, show that it is induced by the accumulation of positive electric charges at the solid‐liquid interface, that diffuse away when pulling is stopped. Under extrinsic electric field, a significant modification of the eutectic phase diagram is observed. The charged diffusive boundary layer interacts with the field and the microstructure is impacted. Those observations suggest that the segregating species is zirconium ions. Abstract : Solidification of Al2 O3 ‐YAG‐ZrO2 :Y eutectic is performed and an intrinsic electric field is measured. Its decay with time and distance, shows that it is induced by the accumulation of positive electric charges at the solid‐liquid interface. Under extrinsic electric field, significant modification of the eutectic phase diagram is observed and the microstructure is impacted.